Reinterpretasi Peran Ideologi Muhammadiyah Terhadap Pemberantasan TBC (Tahayul, Bid’ah dan Churafat) - Rachman, Marlina; Jayanti, Prita Steady; Herniaty; Ramadhani, Sukma Dewi; Pardede, Endi (Penerbit Minhaj Pustaka, 2024)
This research aims to determine the construct of Muhammadiyah ideology. This research is included in the qualitative research category with a literature review as the data collection method. The data used is in the form of concepts and understanding related to Muhammadiyah Ideology, the data sources are books and journals that examine Muhammadiyah Ideology in terms of outlook on life, life guidelines for Muhammadiyah citizens and Muhammadiyah strategies in realizing their life dreams. The data analysis technique uses a simplified approach. The results of the research show that Muhammadiyah Ideology is a set of understandings that contain Muhammadiyah views, life guidelines and strategies in realizing their life ideals. Muhammadiyah's outlook on life is reflected in the muqaddimah of Muhammadiyah's articles of association which contains views on anchor, society, views on Islamic teachings, upholding Islamic teachings, the prophet's arrival in the struggle, organizational views and Muhammadiyah's ideals. Muhammadiyah citizens' life guidelines discuss self- guidelines in religion, socializing in society, organizing and guidelines in state life. There are several Muhammadiyah strategies in realizing its life aspirations which are pursued by developing society related to aqidah, worship and morals, improving the quality of life of the community, developing Muhammadiyah cadres, strengthening Muhammadiyah associations and appropriate political and state strategies. Furthermore, this ideological construct can be used as a basis for developing instruments to measure the strength of Muhammadiyah ideology as well as to eradicate TB (Superstition, Bid'ah and Churafat) community diseases.